Chit’lins and Champagne: Food, Class, and Sexuality in Ann Allen Shockley’s Loving Her - Williams-Forson, Psyche (FRAME, Journal of Literary Studies, 2026)
In her novel, Loving Her, which was groundbreaking in its time for its illustration of interracial love between two women, Ann Allen Shockley uses food to reveal elements of African American Southern cultural identity, but also to elevate Black female self-expression and other manifestations of gender development. Food is also used by Shockley as a vehicle for showing the powerful conflicts and disparities that often exist beneath the surface of romantic relationships, and especially the ways they are informed by gender, race, and class ideologies.